The use of ethnomathematics based on carom media for children's creative thinking - M. Sobri Hidayah; Marsidi Marsidi; Dimas Anditha Cahyo Sujiwo (International Journal of Trends in Mathematics Education Research, 2025)
This study aims to determine students' creative thinking abilities in addition operations using ethnomathematics based on carom media. This study uses a qualitative approach with a descriptive type. The qualitative approach was chosen because this study aims to understand in depth the process of learning mathematics through an ethnomathematics approach using carom media and its impact on children's creative thinking abilities. Data collection techniques were carried out using creative thinking ability tests through essay questions, observation sheets to measure creative thinking abilities, and student interview sheets. Based on the results of the analysis conducted, students' creative thinking abilities have generally shown quite good development. Of the four indicators studied, the aspects of fluency and originality appear more prominent than the other two aspects. Meanwhile, the ability to decompose (elaboration) remains a weakness that requires special attention in the learning process. These findings demonstrate the existence of strengths that can be further developed as well as challenges that need to be addressed. In the fluency indicator, most students are able to generate ideas fluently and quickly. This is evident from 44% of students who are in the very good category and 36% who are in the good category. The originality indicator also shows quite encouraging results. A total of 40% of students were in the excellent category, while 28% were in the good category. In the flexibility indicator, the distribution of student abilities appeared more even. Some students were already in the excellent (32%) and good (24%) categories, but quite a number were still in the fair (28%) and even poor (16%) categories. The elaboration indicator was the weakest aspect. The majority of students (44%) only achieved the adequate category, and only 16% were able to achieve the excellent category. This means that most students still struggle to develop their ideas into more detail and depth. Overall, it can be concluded that students' creative thinking skills are quite good, especially in the aspects of fluency and originality.